Piezotronic PIN diode for microwave and piezophototronic devices. (13th March 2017) - Luo, Lu; Zhang, Yan; Li, Lijie
Abstract: Piezotronics and piezophototronics, the two emerging fields that combine piezoelectric and semiconductor properties of materials have drawn much attention recently. Piezopotential caused by piezocharges can change the energy band and carrier transport of piezoelectric semiconductor materials. The PIN diodes have been widely used in high-frequency microwave circuits. In this paper, we present the theoretical calculations of the piezotronic PIN diode, including the built-in-potential, current–voltage characteristic, and junction capacitance for microwave and radio frequency application. Furthermore, the photovoltaic and luminescence properties of the PIN piezophototronic photodetector and light-emitting diode have been provided under applied strain.